The antihypertensive effect of ethyl acetate extract of radish leaves in spontaneously hypertensive rats - Chung, Da-Hee (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2012)
Radish (Raphanus sativus L.) is a cruciferous vegetable, and its leaves have antioxidant and anticancer properties. This study was conducted to evaluate the effects of ethyl acetate extracts from radish leaves on hypertension in 11-week-old spontaneously hypertensive rats (SHRs). The SHRs were randomly divided into 3 groups of 6 rats each on the basis of initial systolic blood pressure (SBP) and were treated with oral administration of radish leaf extract (0, 30, or 90 mg/kg body weight [bw], respectively) for 5 weeks. Six Wistar rats were used as normotensive controls. The amount of the radish leaf extract had no effect on body weight. The SBP of the SHRs showed a decreasing trend with the consumption of the radish leaf extract. In the third week, the SBP of the group fed 90 mg extract/kg bw reduced from 214 mmHg to 166 mmHg and was significantly lower than that of the normotensive and hypertensive controls. The extract did not show a significant effect on the angiotensin-converting enzyme (ACE) activity in the serum, kidney, and lung. The extract increased the concentration of NO in serum and the activities of antioxidant enzymes such as glutathione peroxidase and catalase in red blood cells (RBCs). The serum concentrations of Na(+) and K(+) were not significantly different between all groups. However, the fecal concentrations of Na(+) and K(+) increased; the fecal concentrations of Na(+) and K(+) for the normotensive and hypertensive controls were not different. Urinary excretion of Na(+) was higher in the normotensive Wistar rats than in the SHRs, while that of K(+) was not significantly different. These findings indicate that consumption of radish leaves might have had antihypertensive effects in SHRs by increasing the serum concentration of NO and fecal concentration of Na(+) and enhancing antioxidant activities.